Didactic Version of Program System for Synthesis and Diagnostics of Logic Circuits - Bača, J.; Korecko, S.; Poruban, J.; Vaclavik, P. (Інститут програмних систем НАН України, 2003)
The Contribution deals with the Internet application of the program system for the synthesis and diagnostics of logic circuits. Internet application contents description of basic notion, theoretical principles and procedure from area of synthesis and diagnostics of logic circuits. This system comprises also programs for solution of logic circuit synthesis and diagnostic tasks. These programs can run in automatic, demo, didactic and test mode. The evaluation of student answers in didactic and test mode are saved to database, which allows analyzing by students or questions. Also the universal virtual learning environment architecture based on this program system is introduced.